Groundwater regulation in case of overdraft: National groundwater policy implementation in north-west China - Eefje Aarnoudse; Bettina Bluemling; Wei Qu; Thomas Herzfeld (International Journal of Water Resources Development, 2018)
This article analyzes why China's national groundwater policy is implemented in a fragmented way. The question is addressed through a comparative case-study analysis of groundwater management in north-west China. The analysis focuses on the institutional context in which local government agencies responsible for groundwater management operate. It was found that direct pressure from the central government promotes policy implementation. Yet, the distribution of surface and groundwater management responsibilities over different government agencies also influences the importance attached to groundwater regulation. In a conjunctive-use setting the integration of surface water and groundwater management facilitates effective groundwater regulation.
Keywords: 320; groundwater regulation; local policy implementation; water policy reforms; comparative case study; China